ANALISIS STILISTIKA PADA IKLAN PROMOSI DI MEDIA DARING (International Forum of Researchers and Lecturers, 2023)
This research is motivated by the existence of one marketplace application. This study discusses the style of language in featured advertisements in the application. Advertising language style has the ability to convince readers by playing words or phrases so that readers are influenced to use the product. The purpose of this study is to analyze and describe the style of advertising language in the shopee application. The method used is descriptive qualitative method. The data in this study is the style of advertising language and the source of the data in the study is advertisements for shopee features that appear on youtube and television. The data collection technique in this study is the method of listening. Based on the results of the discussion on the analysis of the use of advertising language style on YouTube, it can be concluded that the Shopee application uses persuasive language style in the advertisements that are displayed, namely the use of repetition figurehead